Transcriptional Profiling of Non-injured Nociceptors After Spinal Cord Injury Reveals Diverse Molecular Changes - Yasko, Jessica R.; Moss, Isaac L.; Mains, Richard E. (Frontiers in Molecular Neuroscience, 2019)
Traumatic spinal cord injury (SCI) has devastating implications for patients, including a high predisposition for developing chronic pain distal to the site of injury. Chronic pain develops weeks to months after injury, consequently patients are treated after irreparable changes have occurred. Nociceptors are central to chronic pain; however, the diversity of this cellular population presents challenges to understanding mechanisms and attributing pain modalities to specific cell types. To begin to address how peripheral sensory neurons below the injury level may contribute to the below-level pain reported by SCI patients, we examined SCI-induced changes in gene expression in lumbar dorsal root ganglia (DRG) below the site of injury. SCI was performed at the T10 vertebral level, with injury produced by a vessel clip with a closing pressure of 15g for 1 minute. Alterations in gene expression produce long-term sensory changes, therefore we were interested in studying SCI-induced transcripts before the onset of chronic pain, which may trigger changes in downstream signaling pathways and ultimately facilitate the transmission of pain. To examine changes in the nociceptor subpopulation in DRG distal to the site of injury, we retrograde labeled sensory neurons projecting to the hairy hindpaw skin with fluorescent dye and collected the corresponding lumbar (L2-L6) DRG 4 days post-injury. Following dissociation, labeled neurons were purified by fluorescence-activated cell sorting. RNA was extracted from sorted sensory neurons of naïve, sham, or SCI mice and sequenced. Transcript abundances validated that the desired population of nociceptors were isolated. Cross-comparisons to data sets from similar studies confirmed we were able to isolate our cells of interest and identify a unique pattern of gene expression within a subpopulation of neurons projecting to the hairy hindpaw skin. Differential gene expression analysis showed high expression levels and significant transcript changes 4 days post-injury in SCI cell populations relevant to the onset of chronic pain. Regulatory interrelationships predicted by pathway analysis implicated changes within the synaptogenesis signaling pathway as well as networks related to inflammatory signaling mechanisms, suggesting a role for synaptic plasticity and a correlation with pro-inflammatory signaling in the transition from acute to chronic pain.